Kebebasan Berpendapat dan Jerat Digital: Analisis Nullum Crimen Sine Lege dalam Pasal 27 Ayat (3) Undang-Undang ITE dan Relevansinya dengan Pasal 19 Deklarasi Universal Hak Asasi Manusia - Suhandry Aristo Sitanggang; Tajul Arifin; Ine Fauzia (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The fact that the ITE Law's implementation of Article 27 Paragraph 3 fails to meet one of the legality principle's requirements—nullum crimen, nulla poena sine lege certa—motivates this study. “The article does not give the community legal certainty because it is ambiguous and subject to multiple interpretations. One of the fundamental rights guaranteed by the Universal Declaration of Human Rights is the right to free speech. The purpose of this study is to examine digital traps and freedom of speech. It also examines the ITE Law's nullum crimen sine lege premise and how it relates to Article 19 of the Universal Declaration of Human Rights.” This study uses a descriptive analysis method and focuses on a normative legal approach. The information was gathered by searching and analyzing the legal materials in the library. With an emphasis on theoretical analysis of the concepts of freedom of speech and digital snares, the principle of nullum crimen sine lege against human rights, and its implementation in Indonesia, the data analysis technique employs a qualitative legal method, where the data obtained is analyzed deductively. According to the study's findings, Article 27 of the ITE Law is a rubber article that can be interpreted in a variety of ways, raising doubts about its legality. Despite being fundamental, this right might be restricted by law to ensure that human rights, other people's fundamental freedoms, morality, public order, and national interests are recognized and respected. The study's conclusions suggest that in order to prevent misunderstandings and misuse, the article must be precise and unambiguous. Its application must be supported by solid evidence and consistent with the principles of clear article formulation, and it must be balanced with the preservation of free speech. Furthermore, restrictions on freedom of communication must be explicitly outlined in legislation and can only be used to stop defamation, safeguard national security, and stop incitement to violence and hatred.